Cerebral evoked potentials in human chronic Chagas' disease - O. M. Genovese; Olga P. Sanz; J. Correale; Marcela Garcia Erro; R. E. P. Sica (Arquivos de Neuro-Psiquiatria)
Seventy five patients with the diagnosis of chronic Chagas' disease were studied by employing EPs techniques. Two of them had delayed arrival of the signal to the Erb's point and one to the spinal cord when looking at SEPs. TWo patients had increment of the time interval between waves 1st and IIIrd, when studying PEATs. These findings were interpreted as due to peripheral nerve fibers damage, a feature described in previous papers. The, most striking finding was the prolonged time interval between waves N13 and N20 (SEPs) found in two patients and between waves IIIrd and Vth (PEAT) seen in 7 affected subjects. These observations suggested the development of some sort of CNS involvement, perhaps related to myelin damage, in patients who reached the chronic state of the infection.